The basaloid variant of squamous cell carcinoma of the larynx - Tutar,Hakan (2014)
INTRODUCTION: Basaloid squamous cell carcinoma (BSCC) is a rare subtype of squamous cell carcinoma (SCC). Because of its rarity, both clinical and prognostic features of this variant are not well known. OBJECTIVE: In this study, we aimed to determine the frequency of BSCC and other SCC variants among all laryngeal SCC cases, and to determine clinical and prognostic features of BSCC variant. Study design: retrospective cohort study. Evidence level: Level 2b. MATERIAL AND METHODS: Records of the patients who had laryngeal SCC surgically treated at our institute between 2007 and 2013 were retrospectively reviewed. RESULTS: Among 198 subjects who had laryngeal SCC surgically treated, the frequency of the variants of SCC other than classical variant was 10.1% (20/198). The most common SCC variant was BSCC (6.6%). Eleven (84.6%) patients with BSCC were at an advanced stage at the presentation (p > 0.05). The 3-year overall survival and disease-free survival rates were 63% and 53% respectively. CONCLUSION: BSCC variant may be more common than previously reported. Since almost the half of patients experiences disease recurrence in the early period, multimodal treatment strategies should be employed at initial treatment, and a close follow-up is strongly recommended for this aggressive SCC variant.